2015
DOI: 10.4067/s0717-75262015000300004
|View full text |Cite
|
Sign up to set email alerts
|

Prematuros tardíos: estudio clínico retrospectivo de sus causas y consecuencias

Abstract: RESUMENAntecedentes: Los niños nacidos entre las 34 0/7 y 36 6/7 semanas se denominan prematuros tardíos (PT), constituyen 5-7% de los nacidos y poseen mayor morbimortalidad que los niños de término. Objetivo: Analizar las causas de partos PT en nuestra institución. Comparar morbilidad neonatal de nacidos PT y de término. Métodos: Estudio de cohorte retrospectivo. Se revisan registros de nacimientos entre enero de 2009 y diciembre de 2012 identificando los nacidos vivos entre las 34 0/7 y 36 6/7 y entre las 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Premature deliveries might be spontaneous deliveries (unexplained preterm labor or spontaneous rupture of the amniotic membranes) or deliveries caused by medical reasons [2,11]. Nevertheless, it has been reported that up to 20% of induced preterm births are based on clinical experience without a specifically justified medical indication, and whereas some studies have reported that purely elective preterm births might be under 10%, other studies have reported over 50% of non spontaneous late preterm births were non-evidence based [12][13][14]. Moreover, one in five cases could have reached a higher gestational age with fewer future complications [12].…”
Section: Etiology and Consequences Of Prematuritymentioning
confidence: 99%
See 1 more Smart Citation
“…Premature deliveries might be spontaneous deliveries (unexplained preterm labor or spontaneous rupture of the amniotic membranes) or deliveries caused by medical reasons [2,11]. Nevertheless, it has been reported that up to 20% of induced preterm births are based on clinical experience without a specifically justified medical indication, and whereas some studies have reported that purely elective preterm births might be under 10%, other studies have reported over 50% of non spontaneous late preterm births were non-evidence based [12][13][14]. Moreover, one in five cases could have reached a higher gestational age with fewer future complications [12].…”
Section: Etiology and Consequences Of Prematuritymentioning
confidence: 99%
“…Nevertheless, it has been reported that up to 20% of induced preterm births are based on clinical experience without a specifically justified medical indication, and whereas some studies have reported that purely elective preterm births might be under 10%, other studies have reported over 50% of non spontaneous late preterm births were non-evidence based [12][13][14]. Moreover, one in five cases could have reached a higher gestational age with fewer future complications [12]. In France and the USA, nearly 42% of all cesarean sections are performed when the fetus is growing poorly, increasing the birth rate and survival of the PTNB.…”
Section: Etiology and Consequences Of Prematuritymentioning
confidence: 99%